2015
DOI: 10.1016/j.neurobiolaging.2015.02.026
|View full text |Cite
|
Sign up to set email alerts
|

The effects of long-term stress exposure on aging cognition: a behavioral and EEG investigation

Abstract: A large field of research seeks to explore and understand the factors that may cause different rates of age-related cognitive decline within the general population. However, the impact of experienced stress on the human aging process has remained an under-researched possibility. This study explored the association between cumulative stressful experiences and cognitive aging, addressing whether higher levels of experienced stress correlate with impaired performance on 2 working memory tasks. Behavioral performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 50 publications
5
42
0
3
Order By: Relevance
“…Similar findings are reported by a number of cross-sectional studies which state that higher amounts of cumulative stressful events coincide with reduced working memory performance among healthy elderly participants (Dickinson et al, 2011;Tschanz et al, 2012). In addition, rencently published work (Marshall, Cooper, Segrave & Geeraert, 2015) established an inverse relationship between the amount of cumulative experienced stress and cognitive working memory performance among elderly individuals, which was not present among young control participants. Results advocating the adverse effects of stress on cognition among elderly but not young individuals, highlight the possibility of a cumulative impact of experienced stress, which emerges late in life and causes cognitive impairments among the elderly.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar findings are reported by a number of cross-sectional studies which state that higher amounts of cumulative stressful events coincide with reduced working memory performance among healthy elderly participants (Dickinson et al, 2011;Tschanz et al, 2012). In addition, rencently published work (Marshall, Cooper, Segrave & Geeraert, 2015) established an inverse relationship between the amount of cumulative experienced stress and cognitive working memory performance among elderly individuals, which was not present among young control participants. Results advocating the adverse effects of stress on cognition among elderly but not young individuals, highlight the possibility of a cumulative impact of experienced stress, which emerges late in life and causes cognitive impairments among the elderly.…”
Section: Introductionsupporting
confidence: 87%
“…Findings to this effect indicate that Flanker task performance may vary between elderly participants and provide a possible explanation for the discrepant findings in the literature (Zeef & Kok, 1993;. This highlights the importance of considering factors which may exacerbate ageing decline and provides evidence that the impact of experienced stress on ageing is not exclusive to working memory retrieval and maintenance, as evidenced by a number of past studies (Peavy et al, 2009;Dickinson et al, 2011;Marshall et al, 2015), but extends to sensory-motor and inhibitory control performance on executive paradigms. However, with respect to inhibitory control, elderly high stress participants' behavioural shortcomings diverge from those reported in previous papers, as no age differences regarding the increase from congruent to incongruent conditions emerged, but a general deficit extending to both kinds of stimulus arrays.…”
Section: Behavioural Findingsmentioning
confidence: 69%
See 1 more Smart Citation
“…These studies likewise find that an increase in experienced stress reported by elderly individuals throughout their lifetime coincides with reduced cognitive performance when holding age and levels of education constant (Dickinson et al, ; Tschanz et al, ). For example, our own recent work in this respect demonstrated that elderly individuals who experienced high amounts of cumulative stress in the course of their lives performed significantly worse on two working memory tasks, whereas elderly individuals reporting low amounts of cumulative experienced stress showed no decline in performance (Marshall et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…En memoria de trabajo el número de ítems que pueden mantenerse activos disminuye con la edad, las personas mayores son, además, mucho más vulnerables ante tareas que produzcan estrés, complicando la capacidad de mantenimiento de la información y de inhibición de la interrupción. El estrés sería uno de los factores a evitar, ya que se ha observado que la acumulación de experiencias estresantes tendría efectos adversos en el envejecimiento cognitivo general (Marshall et al, 2015). También se produce un deterioro de la memoria a largo plazo, probablemente debido a la atrofia y disminución de la actividad en el hipocampo, concretamente en la zona anterior (Cabeza, 2001).…”
Section: Efecto Del Envejecimiento En La Función Cerebralunclassified